A Hedonic Pricing Model for German Wine - Gun̈ter Schamel (Agrarwirtschaft: Zeitschrift für Betriebswirtschaft, Marktforschung und Agrarpolitik, 2003)
We develop a hedonic pricing model for German quality wine. Quality indicators for 4,141 wines are sensory awards received at the annual German wine competition and the legally required quality category as well as a set of control variables including regional origin, color, style, and their age at the time of judging. The data confirms that sensory quality awards have a significant and positive price impact. Moreover, we estimate significant relative differences between quality categories, growing regions and most of the control variables.
Keywords: 330; Wein; Hedonischer Preisindex; Deutschland